Jane Campion and adaptation: angels, demons and unsettling voices - Tincknell, Estella (Palgrave, 2013)
This book examines Campion's films as adaptations, mixing cultural and textual analysis, and exploring context, pastiche and genre. It is a must-read for anyone interested in Campion or adaptation studies.